2015
DOI: 10.1142/s1758825115400050
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics Modeling of Bi-Axial Stretching Effects on the Electrical Conductivity of CNT-Polymer Composites

Abstract: In this paper, the bi-axial stretching effects on the electrical conductivity of carbon nanotube (CNT)-polymer composites are studied by a mixed micromechanics model with the consideration of the electrical conductive mechanisms. The bi-axial stretching effects are characterized by volume expansion of composite, re-orientation of CNTs and change of conductive networks. Simulation results demonstrate that the bi-axial stretching decreases the electrical conductivity of the composites due to the dominant role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Recently, developing polymer composites with enhanced electrical conductivity and dielectric constant (relative permittivity) has stimulated a surge in academic and industrial communities, due to their great potential in applications such as high-storage capacitors, electromagnetic shielding, and artificial muscles in electrostriction systems [ 36 , 37 ]. The use of carbon nanotubes (CNTs) and/or GNPs as the conductive fillers in polymer composites have been extensively studied [ 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. An electrical conductivity of 2.11 S/m was achieved by Zhang et al [ 55 ] with an addition of only 3.0 vol % of graphene into polyethylene terephthalate (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, developing polymer composites with enhanced electrical conductivity and dielectric constant (relative permittivity) has stimulated a surge in academic and industrial communities, due to their great potential in applications such as high-storage capacitors, electromagnetic shielding, and artificial muscles in electrostriction systems [ 36 , 37 ]. The use of carbon nanotubes (CNTs) and/or GNPs as the conductive fillers in polymer composites have been extensively studied [ 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. An electrical conductivity of 2.11 S/m was achieved by Zhang et al [ 55 ] with an addition of only 3.0 vol % of graphene into polyethylene terephthalate (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Tallman and Wang [40] extended the analytical framework developed by Takeda et al [35] for the piezoresistivity modeling of CNT composites subjected to arbitrary three-dimensional strains. The Eshelby-Mori-Tanaka micromechanics model was also used by Feng and Jiang [31,41] and García et al [42] to simulate the piezoresistivity of CNT reinforced polymers and cement-based materials, respectively. In the latter work, analytical and experimental results demonstrated that the largest strain-sensitivity is achieved at the percolation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant strain ε 1 in X 1 direction due to the bi-axial stretching can be determined by Equation (8), where ν is the Poisson’s ratio of the unit cell. Integrating this expression over the elongations in the three directions, i.e., Δl , Δω and Δh , the strain ε 1 can be derived as [ 57 ] …”
Section: Orientation Distribution Function (Odf)mentioning
confidence: 99%